Changes in arterial blood gases during endoscopy in patients with chronic obstructive lung disease - Yıldıran SONGÜR; Nejla SONGÜR; Himmet KARACA; Ayşe ÖZSÖZ; Sadun KOŞAY (Turkish Journal of Gastroenterology, 2020)
-